Analysis of typical approaches to outpatient management of type 2 diabetes mellitus - Irina Evgen'evna Sapozhnikova; Ekaterina Iosifovna Tarlovskaya; Maria Vladimirovna Avksent'eva; Anastasia Vital'evna Sanatova (Сахарный диабет)
Aim. To analyze typical outpatient management approaches to type 2 diabetes mellitus (T2DM).Materials and Methods. We analyzed 211 files from 7 outpatient clinics, containing case records of patients, regularly examined during2009. VEN, ABC- and frequency analyses were conducted. Results. Prescription percentage for medications with proved prognosis improvement did not substantially differ from recommendedlevel. Main direct expenditures were related to antihyperglycemic, antihypertensive and hypolipidemic agents (class V). Inexpensivemedications without proven efficiency (class N) were prescribed more frequently than those with capacity to improve quality of life(class E). Testing for HbA1c level was found to be of inadequate frequency and thus complicated assessment of antihyperglycemic treatmentefficacy. Number of patients with improvement in arterial hypertension showed an increase, but treatment goals were not achievedin 2/3 of patients (according to office measurement). Prescription frequency of statins, though growing in the course of year, remainedinsufficient; rare testing for LDL complicated assessment of hypolipidemic treatment adequacy. Conclusion. Structure of pharmacological treatment is fairly adequate, but goals of multifactor therapy are not achieved in a significantpercentage of patients, which may be explained by peculiarities of diabetes pathogenesis, prescription of inadequate treatment regimensand doses and insufficient dynamic control.